E0451 Combined use of oxidised low density lipoprotein and C-reactive protein for the prediction of the acute coronary syndrome. (17th November 2010) - Ya-chen, Zhang; Jingjing, Wei; Mantian, Chen; Qing, Zhou; Shu, Meng; Yigang, Li
Abstract : Background: Serum CRP levels can predict future risks among patients with stable and unstable angina, but CRP was easy infected by many factor. Increased blood levels of ox-LDL could play a role in these circumstances. However, Combined detection of ox-LDL and CRP for the prediction of the acute coronary syndrome are not known. Methods: All of the patients received a coronary angiography owing to complaining of chest pain. The coronary artery disease dianosis and stenosis severity was judged by two independent experts and the patients were accounting Gensini Score. The serum oxLDL and high sensitivity C-reactive protein (hs-CRP) levels were measured using a sandwich ELISA method. The MACEs of documented CAD patients were recorded in the one year follow-up period. SPSS software was chosen to analyse the influence of Oxidised Low Density Lipoprotein and C-reactive protein on the incidence of MACE. Results: (1) In acute myocardial infarction patients, ox-LDL and hs-CRP levels were significantly higher than in patients with unstable angina pectoris (p<0.01) or stable angina pectoris patients (p<0.01) or in controls (p<0.01) (acute myocardial infarction, oxLDL 177.5 mmol/l, hs-CRP 21.4 mg/l; unstable angina pectoris, oxLDL 97.5 mmol/l, hs-CRP 6.7 mg/l; stable angina pectoris, oxLDL 62.3 mmol/l, hs-CRP 3.7 mg/l; Control, oxLDL 41.7 mmol/l, hs-CRP 2.7 mg/l). (2) A positive correlation between the serum levels of oxLDL and CRP with the severity in patients with coronary artery disease. (3) Combined use of Oxidised Low Density Lipoprotein and C-reactive protein can predict the severity in patients with acute coronary syndrome and the risk for major adverse cardiac event (MACE) in patients with acute coronary syndrome (p<0.005). Conclusions: This study demonstrates that ox-LDL and hs-CRP levels show a significant positive correlation with the severity of acute coronary syndromes. These findings support the hypothesis that ox-LDL and CRP may play a direct role in promoting the inflammatory component of atherosclerosis. The results suggested that combined use of Oxidised Low Density Lipoprotein and C-reactive protein can predict the acute coronary syndrome. The patient with higher level of ox-LDL and CRP suffer from the higher risk of MACE.